Identifying The Effectiveness Of Internal Audit Quality In The Government Of North Sumatra - Muhammad Irsan Nasution; Yulisfan (Yayasan Multidimensi Kreatif, 2023)
The purpose of this study was to determine the identification of the effectiveness of internal audit quality in the North Sumatra government. The research data were obtained from questionnaires sent to respondents, namely auditors in the provincial and district / city regional directorates in North Sumatra. A total of 130 usable questionnaires were included in the multiple regression data analysis. This study provides valuable information for inspectorates and local governments in North Sumatra to determine the effectiveness of internal quality in the North Sumatra government. The challenge facing auditors today is to expand their audit practices and develop standards to adequately monitor the operations of business entities. The current high turnover rate reminds audit firms, which are concerned with training and providing sufficient resources to solve the problems auditors face in the workplace. Identifying the effectiveness of internal audit quality can be assessed from many factors, including task complexity.